Learning Techniques Smash Volleyball Game Large Scale Trials - Destriana Destriana; Destriani Destriani; Muslimin Muslimin (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2021)
The purpose of this study was to develop the volleyball game drill smash learning technique for the students of Universitas Sriwijaya Phisical education. This study uses a mixed approach, Research and Development research methods. This study uses observation instruments and questionnaires as a means of collecting data. The research steps consisted of needs analysis, product draft planning, expert validation, small-scale trials, product revisions, large-scale trials and revisions. This study used 3 validation experts, namely Physical Education experts, volleyball game experts and linguists, with the small-scale test subjects of 24 UNSRI Physical Education students, and 105 students for large-scale trials. The research resulted in 12 drill smash learning techniques that were declared valid from 3 experts, namely with an average of 82.3%, small-scale trials obtained an average result of 88.9% of students who could use this development technique and get 95.54% results and not There are significant prohibitions in large-scale trials so that this learning development technique is suitable for use in volleyball smash learning. The development of 12 volleyball drill smash learning techniques that can be used for Physical Education students, especially the volleyball game smash material and can be used by teachers as an added reference in teaching volleyball games are the findings of this study.